The Emerging Role of Wearable Technologies in Detection of Arrhythmia - Cheung, Christopher C.; Krahn, Andrew D.; Andrade, Jason G. (Canadian journal of cardiology, 2018)
Over the past decade, there has been an explosion of consumer devices for the purposes of health and fitness tracking. The wearable technology market, composed of devices that monitor physiological parameters, such as heart rate and sleep pattern, is anticipated to grow to 929 million connected devices in 2021. These devices encompass wristbands, glasses, in-ear monitors, or electronic shirts, with varying capacity to monitor heart rate, heart rhythm, blood pressure, physical activity, respiratory rate, blood glucose, and sleep patterns. For heart-rate monitoring, most wearable devices use photoplethysmography (PPG) technology, meaning they are inherently less accurate than conventional electrocardiography monitoring techniques (reference standard). However, a growing body of evidence suggests that these technologies can be harnessed to facilitate arrhythmia detection in the appropriate context. Studies evaluating PPG-based wearables in conjunction with machine-learning algorithms have shown promise in detection of such arrhythmias, as atrial fibrillation. Limitations of wearable technologies include their accuracy and accessibility and the clinical implications of wearable-detected arrhythmias. Despite this, wearable technologies represent an important frontier in health evaluation. Future wearables will benefit from improved reliability and accuracy, collect additional health and fitness parameters, support management of chronic disease, and provide real-time connectivity and feedback that may supplant conventional medical monitoring. Wearables have the potential to become truly disruptive in our health care sector, with large segments of the population soon to have readily available health data that the physician must interpret. Au cours de la dernière décennie, il y a eu explosion des dispositifs grand public dans le but de suivre la santé et la condition physique. Le marché de la technologie portable, composé d’appareils qui surveillent les paramètres physiologiques tels que la fréquence cardiaque et la structure du sommeil, vont atteindre jusqu’à 929 millions d’appareils connectés en 2021. Ces appareils englobent les bracelets, les lunettes, les moniteurs intra-auriculaires ou les vêtements électroniques dont la capacité à surveiller la fréquence cardiaque, le rythme cardiaque, la pression artérielle, l’activité physique, la fréquence respiratoire, la glycémie et les cycles du sommeil varie. En ce qui concerne la surveillance de la fréquence cardiaque, les appareils les plus portables utilisent la photopléthysmographie (PPG); ils sont donc intrinsèquement moins précis que les techniques d’électrocardiographie traditionnelles (étalon de référence). Toutefois, de plus en plus de données probantes montrent que ces technologies peuvent être utilisées pour faciliter la détection de l’arythmie dans un contexte approprié. Les études visant à évaluer les portables qui utilisent la PPG conjointement avec les algorithmes d’apprentissage automatique se sont révélées prometteuses dans la détection de certaines arythmies comme la fibrillation auriculaire. Malgré cela, les technologies portables constituent une frontière importante dans l’évaluation de la santé. Les futurs portables bénéficieront d’une fiabilité et d’une précision accrue, permettront de collecter d’autres paramètres sur la santé et la condition physique, favoriseront la prise en charge des maladies chroniques et fourniront une connectivité et une rétroaction en temps réel qui pourraient supplanter la surveillance médicale traditionnelle. Les portables risquent de véritablement perturber notre secteur des soins de santé puisque bientôt de larges segments de la population auront des données sur la santé facilement accessibles que le médecin devra interpréter.